HUMANITARIZATION OF HIGHER TECHNICAL EDUCATION: PSYCHOLOGICAL AND PEDAGOGICAL ASPECT (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the organization of studying psychological and pedagogical subjects for students of technical universities.